Factor shares analysis of livestock products in selected areas of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
A study was undertaken to assess the contribution of different inputs such as feed, labor veterinary services and depreciation cost etc. to the development of livestock sector including poultry in the study area. The factor shares of livestock products was estimated based on the primary data for the periods of April to July, 2012.The factor shares of livestock production suggested that current factors (Feed, hired labor, veterinary services and other inputs) and family labor was the major component in the livestock production. Traditional milk producing farmers in Gazipur were not benefited from their farming due to residual share was negative (-11.15%). For commercial milk production, on an average the largest share current factors (60.54 percent) followed by residual (28.1 percent), family labor (6.63 percent), depreciation (4.74 percent), respectively and residual share was positive. Production of beef cattle on an average the largest share current factors (74.26 percent) followed by family labor (21.73 percent), depreciation (46.425 percent), respectively and residual share was negative (-2.41 percent). Production of egg by traditional management was found profitable enterprise in small and large categories of farms. As a result, residual share was positive (1.54 percent and 12.01 percent) for small and large farms. In case of commercial poultry production on an average the largest share current inputs (74.29 percent), residual ((19.64 percent), followed by family labor (5.64 percent) and depreciation (0.44 percent) respectively. In addition, on an average broiler production the largest share current inputs (84.18 percent), residual (12.53 percent), followed by family labor (2.68 percent) and depreciation (0.62 percent) respectively.Asian J. Med. Biol. Res. June 2016, 2(2): 196-201